Pelatihan Bahasa Inggris Kreatif dan Inovatif Menggunakan Aplikasi Duolingo pada Siswa SD IT Maarif Padang Panjang - Vonny Ardiel; Dina Ayuning Tyas (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Learning English today has a variety of creative and innovative ways to attract children's interest and get good learning outcomes. English language skills are skills that are needed in this globalization era. English is the main communication tool in education as well as general interaction in national and international society. For this reason, we carry out community service with creative and innovative English language training programs using the Duolingo application for students at SDIT Maarif Padang Panjang. Initial observations were made by looking at the needs and schedule for implementing English learning at SDIT Maarif. Then, the English learning schedule is carried out in grade 4 in the second semester. For this reason, we asked the school for a schedule at the end of semester one with the aim of providing motivation and introduction to English to participants using technology. The results obtained in this program are the participants' relatively high interest in learning English with the Duolingo application because it is very interesting, sophisticated and easy to understand learning material. Participants get an understanding of English material both in English vocabulary, pronunciation, listening, and grammar because the Duolingo application trains participants efficiently